Kompetensi Hakim dalam Gugatan Sederhana Sengketa Ekonomi Syariah di Pengadilan Agama Bantul - Dewi Mariyatul Qibtiyah; Abdul Mujib (Media of Law and Sharia, 2023)
This study examines the competence of judges in simple lawsuits for sharia economic disputes at the Bantul Religious Court (Decision Study Number 2/Pdt.G.S/2019/PA.Btl). The focus of the research is the opportunity for disputes over objects that serve as collateral in multiservice ijarah financing agreements. The purpose of this study is to determine the competence or authority of judges regarding these sharia economic disputes. The research method used is a normative juridical research type, in which research is aimed at written regulations or legal materials in the form of court decisions, namely decision Number 2/Pdt.G.S/2018/PA.Btl. Sources of data in the form of decisions, laws and PERMA are outlined in the form of narrative descriptions, not transformed into numbers. Then analyzed deductively in accordance with the theoretical framework used. The results of this study are the defendant's guarantee cannot be executed because it is a land dispute and the judge is not authorized to examine and adjudicate the dispute, because land disputes cannot be resolved through a simple lawsuit. So that the case was crossed out from the case register at the Bantul Religious Court and could be re-registered to be resolved through an ordinary procedural lawsuit.